Constraints on models of scalar and vector leptoquarks decaying to a quark and a neutrino at s =13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2018)
The results of a previous search by the CMS Collaboration for squarks and gluinos are reinterpreted to constrain models of leptoquark (LQ) production. The search considers jets in association with a transverse momentum imbalance, using the MT2 variable. The analysis uses proton-proton collision data at ffiffi s p ¼ 13 TeV, recorded with the CMS detector at the LHC in 2016 and corresponding to an integrated luminosity of 35.9 fb−1. Leptoquark pair production is considered with LQ decays to a neutrino and a top, bottom, or light quark. This reinterpretation considers higher mass values than the original CMS search to constrain both scalar and vector LQs. Limits on the cross section for LQ pair production are derived at the 95% confidence level depending on the LQ decay mode. A vector LQ decaying with a 50% branching fraction to tν, and 50% to bτ, has been proposed as part of an explanation of anomalous flavor physics results. In such a model, using only the decays to tν, LQ masses below 1530 GeV are excluded assuming the Yang-Mills case with coupling κ ¼ 1, or 1115 GeV in the minimal coupling case κ ¼ 0, placing the most stringent constraint to date from pair production of vector LQs.